Outcomes of endovascular treatment in acute ischemic stroke patients with current malignancy - Cho, Bang-Hoon; Yoon, Woong; Kim, Joon-Tae; Choi, Kang-Ho; Kang, Kyung-Wook; Lee, Jin-Heui; Cho, Ki-Hyun; Park, Man-Seok (Neurological sciences, 2020)
Background and purposes The role of endovascular recanalization in the treatment of cancer patients with acute stroke remains elusive. Our study aimed to investigate the clinical and imaging outcomes of endovascular recanalization treatment in patients with acute large vessel occlusion stroke who had active cancer. Methods We retrospectively reviewed the data from our stroke registry from January 2011 to September 2016 which was collected prospectively. Acute stroke patients with large artery occlusion in the anterior circulation who had active cancer were identified. Baseline clinical characteristics and postprocedural and long-term clinicoradiological outcomes were evaluated. A good outcome was defined as a 90-day modified Rankin Scale score of 0 to 2. Outcomes were also compared with those of non-malignancy patients who had received endovascular therapy during the same period. Results A total of 378 ischemic stroke patients received endovascular treatment, of whom 27 (7.14 %) had current malignancy. In patients with current malignancy, a low baseline NIHSS score and male sex were associated with functional independency at 90 days. When comparing with non-malignancy patients, no significant differences in the proportions of patients with symptomatic intracranial hemorrhage (11.1% vs 16.2%, p = 0.60) and good functional outcome (37.0% vs 39.6%, p = 0.84) were found in the malignancy patients. Conclusion Endovascular treatment might be a feasible therapeutic option for acute ischemic stroke patients with current malignancy when candidates are selected carefully because the outcomes were not differed. Future large-scale prospective studies are necessary.